Ticks and Tick-Borne Pathogens - Abubakar, Muhammad; Perera, Piyumali K. (IntechOpen, 2019)
It is vital to understand ticks and tick-borne pathogens as well as their impact on humans. This book is intended for students in parasitology, biologists, parasitologists involved in molecular diagnostics of tick-borne diseases, practicing veterinarians, and for others who may require information on ticks and tick-borne diseases. Here we have put together a collection of chapters focused on different aspects of ticks and tick-borne diseases mainly to provide the reader with novel information in the field, but not the basic generalised information provided by many textbooks. This book includes topics such as high-throughput technologies in diagnosis, discovery of novel tick vaccines, identification of new pathogens transmitted by ticks, and new epidemiological information of certain well-known ticks and tick-borne diseases. These chapters were authored by parasitologists from all over the world, giving an insight to the reader about significant ticks and tick-borne diseases prevalent in those particular geographical regions with the local expert's point of view. Each of the chapters has separate reference lists, making it easier for the reader to find additional reading material related to their topic of interest.